Heat transfer prediction for a direct contact ice thermal energy storage - Kiatsiriroat T. (2014)
This research work studies the heat transfer characteristics of a direct contact evaporator. A cold two phase refrigerant (R12 or R22) is injected into water kept in a storage tank to exchange heat with the water directly. The water temperature is reduced to the freezing point, and ice could be formed. The lump model is used to predict the water temperature, and it is found that this model can predict the water temperature quite well. A correlation that relates the dimensionless parameters, such as Stanton number, Stephan number, Prandtl number and pressure ratio, is also developed. © 2002 Elsevier Science Ltd. All rights reserved.